Iron bioaccessibility and sensory analysis of extruded cereals fortified with different Fe sources - Cagnasso, Carolina Elisa (2013)
To increase iron (Fe) intake in Fe deficiency-risk groups the combination of Fe source and food-vehicle must be chosen in order to minimize inhibitory effects of food matrix. Fe dialyzability and sensory properties were tested in six model systems (MS) made with extruded cereals fortified with different Fe sources such as FeNaEDTA, FeSO4 and EDTA/FeSO4 among others and with or without the addition of milk. Proximate composition and phytate content were also evaluated. Results showed that Fe dialyzability from samples fortified with FeNaEDTA was less affected by the presence of inhibitory factors such as phytates and milk. The addition of FeSO4 to the extrudates showed sensory differences. Furthermore, fortification with EDTA/FeSO4 or FeNaEDTA showed no sensory differences compared with unfortified or Feº (elemental iron) fortified matrix, with the advantage of increased iron bioaccessibility.